Appropriability, patents, and rates of innovation in complex products industries - Luigi Marengo; Corrado Pasquali; Marco Valente; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
The economic theory of intellectual property rights is based on a rather narrow view of both competition and technological knowledge. We suggest some ways of enriching this framework with a more empirically grounded view of both and, by means of a simulation model, we analyze the impact of different property right regimes on the dynamics of a complex product industry, that is an industry where products are complex multi-component objects and competition takes place mainly through differentiation and component innovation. We show that, as the complexity of the product spaces increases, stronger patent regimes yield lower rates of innovation, lower product quality and lower consumers' welfare.
Keywords: O31; O34; L11; 330; patents; appropriability of innovation; complex product industries; industrial dynamics